The combination effect of Naphthalene Acetic Acid (NAA) and Benzyl Amino Purine (BAP) in micro propagation of castrol oil plant (Jatropha curcas L.) - Meutia Zahara; Zairin Thomy; Essy Harnelly (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2011)
The fossil energy reservation decreases day by day, this situation impacted to the   energy crises especially fuel energy which is increasing in the price on over the world. The scientists/researchers are trying to develop the renewable energy (renewable fuel) as the energy  alternative, one of these called biodiesel. Taking the benefit from Jatropha curcas’ seed as raw  material         for the fuel is one of the alternative ways to reduce the fuel demand and also can save the  countries’   foreign exchange. J. curcas’ oil is renewable fuel and non edible oil, so that it will not  compete with oil   consumption, such as palm oil, corn oil, etc. The combination between Naphthalene acetic acid (NAA) (1-                   2 ppm) and Benzyl Amino Purine (BAP) (0,5 and 1 ppm) for            micro propagation of Castrol oil plant (Jatropha curcas L.) was tried to induce the callus formation by using the meristem shoot as the explants. The result showed that the combination of NAA 1.5  ppm and BAP 0,5 ppm gave the best result for the callus formation.